Host innate and adaptive immunity shapes the gut microbiota biogeography. (26th May 2022) - Gu, Min; Samuelson, Derrick R.; de la Rua, Nicholas M.; Charles, Tysheena P.; Taylor, Christopher M.; Luo, Meng; Siggins, Robert W.; Shellito, Judd E.; Welsh, David A.
Abstract: The gut microbiota has a fundamental role in the development and the maturation of the host immune system. Both innate and adaptive immune cells have critical functions in microbial pathogen containment and clearance, but the regulation of the commensal microbiome ecosystem in the gastrointestinal tract by these major immune cell populations is incompletely defined. The role of specific innate and adaptive immune cell in the regulation of the microbiota in the intestinal tract biogeographically was investigated. Dendritic cells, macrophages, CD4+ T‐cells, CD8+ T‐cells, and B‐cells were depleted using monoclonal antibodies and clodronate liposomes, and the microbial communities were determined by 16S rRNA gene sequencing. With specific immune cell depletion, distinct microbiota changes were observed. In general, immune cell depleted mice had higher microbiota richness and evenness at all gut anatomical sites. At each gut segment, samples from immune cell‐depleted animals clustered away from the isotype/liposome control mice. This was especially dramatic for the small intestinal microbiota. Specifically, Enterobacteriaceae, Bacteroides acidifaciens, and Mucispirillum schaedleri were highly enriched in the mucosa and lumen of the small intestine in immune cell‐deficient animals. Further, the mucosal microbiota had higher microbiota evenness compared with luminal microbiota at all gut segments, and the UniFrac distance between B cell depleted and isotype control mice was the largest in the duodenum followed by the ileum and colon. Taken together, the data suggest that innate and adaptive immune cells specifically contribute to the regulation of the gut microbiota's biogeographical distribution along the gastrointestinal tract, and microbiota in the duodenum mucosa are more responsive to host immune changes compared with other anatomical sites.